Korelasi Motivasi Belajar Terhadap Prestasi Belajar Siswa Kelas IV Di Madrasah Ibtidaiyah Muhammadiyah 04 Blimbing Paciran - Suntari Daip; journal journal (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Learning is an activity that proceeds and is a very fundamental elementin the implementation of each type and level of education. This means that thesuccess or failure of the achievement of the educational objectives depends verymuch on the learning process that students experience when they are at school orin their home or family. Based on the background of the above problem, then theformulation of the problem as follows: What is the learning motivation of studentsof class X Subject PAI In SMKN 13 Malang and Is there a correlation of learningmotivation with student achievement class X Subject PAI In SMKN 13 Malang.The method used in data collection is descriptive method. While the approachtaken is a quantitative approach. Data collection in this study includes literaturestudy and field study. The implementation of this field study involves observationtechniques, interviews, and using data collection instruments in the form ofquestionnaires. Based on the results of correlation analysis obtained 0,538. Inorder for this number to be meaningful, it needs to be interpreted so as to give anexplanation of the correlation between learning motivation and studentachievement, that is by consulting through the value of r on the product momenttable, either with a significance level of 5% or 1%. For more details will beinterpreted r o and r t (table) as follows. At the level of significance of 5% with thenumber of respondents (N) = 22 obtained r t = 0.423, while r o = 0.538. Thus r ois greater than r t or in other words r o> r t. This means indicating a significantor positive correlation between the two variables. At the level of significance of1% with the number of respondents (N) = 22 obtained r t = 0.537, while r o =0.538. Thus r o is greater than r t or in other words r o> r t. This meansindicating a significant or positive correlation between the two variables. So thehypothesis examined that